A Study On The Utilization and Health Services Provision by Community Clinics of Jashore, Bangladesh (Epidemiology, Biostatistics, and Public Health, 2022)
Background: As Bangladesh has gained the reputation of improving the health sectors, much health related sites still require improvements. Community clinic services (CCS) may contribute to this sector with its foremost importance. So this study was conducted to investigate the utilization and health services provision by community clinics (CCs) in rural area.Methods: A descriptive longitudinal study was conducted among three community clinics of Jashore and a structured questionnaire was developed on which most of the questions were developed to find out the contributions of these community clinics. Here for data analysis we used SPSS version 25.0 software.Results: Here we analyzed health service related data from three randomly selected community clinics (CCs). We found an average of 15 patients got antenatal care every month by the Komlapur CC throughout the year. About 140 patients received health services per month from Dogachiya CC. About 634 children were benefited by Saziyali CC throughout the year. By this study we came to know that average 67-75 patients were provided iron supplementations each month by Saziyali CC. All of the CCs had active referral system and online reporting system.Conclusion: From our study we came to know that majority % of rural people are now dependent on community health care services. But most of the community clinics have many limitations regarding infrastructure, training, medicines, financial etc. So the government should take necessary steps regarding this.